Os romances de amor nas transformações da cultura digital contemporânea (2013-2021) - Oliveira, Paulo Henrique de (2022)
Romances of love, of the heart, sentimental, pink, of a little woman, sugar water, are some of the terms used to refer to literature that has, as one of its main characteristics, narrating the love story between a couple who fall in love. and face challenges. However, at the end of the narratives, in a sense of completeness, they achieve their happy ending. These different denominations, in addition to referencing them, also characterize the long trajectory of this literature, both in the national and international literary scene. Looking at its historical roots, it is noted that love novels have been produced since the 18th century, certainly with due regard for their forms of production and circulation at different times and places. Therefore, like all literature in its essence, this one carries meanings, whose expressions that were attributed to it, to a certain extent, symbolize them. In Brazil, from the 2010s onwards, new paths were opened for this literary production, facilitated by digital resources, such as publishing platforms and online social networks, which allow authors in the segment to publish and disseminate them in other ways, especially in the cyberspace. This thesis aims to understand the new arrangements that are established in the production and dissemination of love novels in the light of the memories of ten Brazilian authors about their experiences in this literary field. It proposes to think about contemporary digital culture, partly characterized by the numerous electronic devices connected to the internet that promote the virtualization of habits, as the scenario in which the set of transformations occurs for those who write and publish love novels. The authors' testimonies served as a horizon to read this conjuncture of the practices they develop in their literary work, the specificity of their narratives and the autonomous constitution of their field of action. Aspects that configure the transformations pointed out by this thesis. They are, therefore, paths that are beginning to be established for those who write, publish and even read love novels in the present time